Faktor Penguat Yang Berhubungan dengan Kecanduan Penggunaan Smartphone Pada Remaja dengan Pendekatan Precede Proceed Model - Irwina Angelia Silvanasari; Trisna Vitaliati (Jurnal Kesehatan dr. Soebandi, 2019)
Excessive use of internet access causes adolescent smartphone addiction. The reinforcing factor in the behavior of smartphone usage is inseparable from parent and peer roles. The purpose of this study was to analyze the reinforcing factors associated with smartphone addiction in adolescent with the Precede-Proceed Model approach. This research method used observational analytic: cross sectional approach. This research was conducted at Stikes dr. Soebandi Jember. The sample of this study were 51 adolescents using multistage random sampling. The independent variable is parent role and peer role. The dependent variable is smartphone addiction. The results of this study found that there was a significant relationship between parent role with addiction of smartphone usage with p value <α (0.01 <0.05). There is a significant relationship between the peer role with addiction of smartphone usage with p value <α (0,000 <0.05). Adolescents who have a poor parental role have smartphone addiction. Adolescents who have a poor peer role also cause smartphone addiction. Excessive use of smartphone should be minimized by adolescents. Parents should pay more attention to the smartphone usage in their children. Parents should also play a role in limiting smartphone usage. Peers should also provide a good environment related to the wise use of smartphone in adolescents and present themselves as real friends for tadolescent